Premarital Screening: A Catalyst for Achieving Good Health and Well-Being - Sidabutar, Nadya Hanna Talitha; Ella Nurlaella Hadi (Jurnal Promkes: The Indonesian Journal of Health Promotion and Health Education, 2024)
Background: Premarital screening is a comprehensive examination that must be done before marriage, which includes examinations of reproductive organs, genetic diseases, infectious diseases, and blood-borne infections. The screening aims to avoid the risk of long-term diseases for couples and their descendants. This screening can also prevent maternal and infant mortality, birth defects, and stunting because risk factors can be detected and addressed early in the mother and baby-to-be. Despite its importance, premarital screening behavior is not culturally embedded. Aims: This study aimed to determine factors associated with premarital screening behavior. Methods: This research uses systematic review as its design from Google Scholar and Scopus databases that discuss the determinants of premarital screening behavior with quantitative methods. Articles were collected with the keywords "premarital" and "screening" published within the last five years, from 2018 to 2023. Results: The researchers discovered 1,151 articles. 10 articles fulfilled the criteria and objective of this study and were further reviewed. Older age, female, higher education level, consanguineous relationship between parents, history of genetic diseases, good knowledge and positive attitude, and the establishment of government regulations are factors associated with premarital screening behavior. Conclusion: Health promotion may be expanded to raise public awareness of the necessity of premarital health screening. It is also intended that future researchers would investigate premarital health screening behavior using various research approaches, such as cross-sectional or qualitative research.